Nowakowskiella moubasheriana sp. nov., a new cladochytrioid fungus from Poland - S. K. Hassan (Acta Mycologica, 2014)
A new exooperculate species of Nowakowskiella has been described. The type strain has been isolated from the water sample taken from the small bog in the ash forest in the National Kampinos Park near Warsaw. The fungus developed on bits of onion skin the rhizomycelial growth and formed numerous zoosporangia and resting spores. It is considered by the author to be a new species of Nowakowskiella related to N. macrospora Karling, and named N. moubasheriana sp. nov.